2011
DOI: 10.1016/j.bbmt.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Graft-versus-Host Disease

Abstract: The gastrointestinal (GI) tract is the main target site of graft-versus-host disease (GVHD). Diagnosis is based on endoscopic and histological findings. Helicobacter pylori (HP) is a Gram-negative spiral bacterium linked to gastritis, peptic ulcer disease, gastric mucosa-associated lymphoid tissue lymphoma, and adenocarcinoma and is frequently observed on endoscopy in patients who have undergone transplantation. The role, if any, played by HP infection in the development of acute GVHD is unknown. We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although in the paper by Correia-Silva et al, 38 no relationship between HP infection and the development of GvHD was observed in 46 patients who received an allogeneic transplant, our group reported in a retrospective study 15 with 198 patients that HP infection had a negative modulating effect on the development of acute GvHD (RR = 0.60 (95% CI: 0.46-0.79) P = 0.001) and chronic GvHD (RR = 0.75; (95% CI: 0.61-0.92) P = 0.016). Furthermore, the presence of HP was inversely correlated with the histological severity of GvHD (P = 0.003).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although in the paper by Correia-Silva et al, 38 no relationship between HP infection and the development of GvHD was observed in 46 patients who received an allogeneic transplant, our group reported in a retrospective study 15 with 198 patients that HP infection had a negative modulating effect on the development of acute GvHD (RR = 0.60 (95% CI: 0.46-0.79) P = 0.001) and chronic GvHD (RR = 0.75; (95% CI: 0.61-0.92) P = 0.016). Furthermore, the presence of HP was inversely correlated with the histological severity of GvHD (P = 0.003).…”
Section: Discussionmentioning
confidence: 85%
“…This represents a significant selection bias. 15 We now report our results from a prospective study of patients whose HP infection state was determined before transplant. The hypothesis to be tested was that pre-HCT HP infection was associated with a lower frequency of GI-GvHD than in HP-non-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Graft-versus-host disease (GVHD) is a complex pathogenic immunological consequence of allogeneic hematopoietic stem cell transplantation (allo-HSCT) that causes injury to specific organs like the gastrointestinal (GI) tract, liver, and skin and leads to significant clinical mortality and morbidity. Damage to these target tissues is incurred from the alloreactive donor T cells that recognize the disparate major or minor histocompatibility antigens on the host tissues ( 1 5 ). Strategies to prevent and alleviate GVHD focus exclusively on suppressing immune responses, which might result in infectious complications and relapse of the primary disease.…”
Section: Introductionmentioning
confidence: 99%